2019
DOI: 10.3389/fphar.2019.01229
|View full text |Cite
|
Sign up to set email alerts
|

Patchouli Essential Oil and Its Derived Compounds Revealed Prebiotic-Like Effects in C57BL/6J Mice

Abstract: Pogostemon cablin (Blanco) Benth (PC) is a Chinese medicinal plant traditionally used for the treatment of gastrointestinal symptoms. To investigate the prebiotic effect of patchouli essential oil (PEO) and its derived compounds through the modulation of gut microbiota (GM). C57BL/6J mice were treated with the PEO and three active components of PEO, i.e. patchouli alcohol (PA), pogostone (PO) and β-patchoulene (β-PAE) for 15 consecutive days. Fecal samples and mucosa were collected for GM biomarkers studies. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Meanwhile, Bacteroides , Escherichia , Helicobacter , and Parabacteroides are closely associated with intestinal inflammation and disease severity [43] . The positive effects of PA on intestinal barrier function and gut microbiota were further supported by a study investigating the prebiotic activity of PA in mice of normal condition [28] . Oral administration of PA (20 mg/kg) for 15 consecutive days improved intestinal epithelial barrier function, evidenced in increased E-cadherin/N-cadherin ratio and tight junction markers (ZO-1 and occludin).…”
Section: Health Beneficial Effects Of Pamentioning
confidence: 83%
See 3 more Smart Citations
“…Meanwhile, Bacteroides , Escherichia , Helicobacter , and Parabacteroides are closely associated with intestinal inflammation and disease severity [43] . The positive effects of PA on intestinal barrier function and gut microbiota were further supported by a study investigating the prebiotic activity of PA in mice of normal condition [28] . Oral administration of PA (20 mg/kg) for 15 consecutive days improved intestinal epithelial barrier function, evidenced in increased E-cadherin/N-cadherin ratio and tight junction markers (ZO-1 and occludin).…”
Section: Health Beneficial Effects Of Pamentioning
confidence: 83%
“…Moreover, PA showed intestinal immunosuppressive activity in terms of down-regulation of immune cell adhesion molecules (ICAM-1 and VCAM-1) and pro-inflammatory cytokines (IL-18 and TNFα) and upregulation of anti-inflammatory cytokines (IL-4 and IL-10). Interestingly, the immunosuppressive properties of PA might result from inactivation of polarization to M1-type macrophages, evidenced by down-regulation of the proinflammatory M1-type macrophage marker (iNOS and CXCL10); PA showed no effect on the anti-inflammatory M2-type macrophage marker (Arginase 1 and mannose receptor) [28] . Moreover, the effect of PA on intestinal barrier function might result from gut microbiota modulating activity of PA. PA increased the abundance of lactic acid-producing bacteria ( L. johnsoni and L. reuteri ) and short chain fatty acid (SCFA)-producing bacteria ( Prevotella spp., C. jejunese , and C. populeti ), along with enhancing SCFA-sensing receptors (GPR41 and GRP43) in intestinal tissue [28] .…”
Section: Health Beneficial Effects Of Pamentioning
confidence: 99%
See 2 more Smart Citations
“…The results of several studies have suggested that PO and its derivatives, including pogostone, PA, and β-PAE, serve to support the function of the gut epithelial barrier, to facilitate the polarization of M1 to M2 macrophage phenotypes, to increase the diversity of the GM, and to suppress the pro-inflammatory cytokines in mouse model systems. Taken together, these results suggest that the pharmacological activities of PA, pogostone, and β-PAE contribute to the dynamic interactions between the host and the GM [ 135 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%